2020
DOI: 10.1021/acs.jafc.0c01476
|View full text |Cite
|
Sign up to set email alerts
|

Oleanane- and Ursane-Type Triterpene Saponins from Centella asiatica Exhibit Neuroprotective Effects

Abstract: Six new pentacyclic triterpenoid saponins, centelloside F (1), centelloside G (2), 11-oxo-asiaticoside B (3), 11-oxomadecassoside (4), 11(β)-methoxy asiaticoside B (5), and 11(β)-methoxy madecassoside (6), along with seven known ones, asiaticoside (7), asiaticoside B (8), madecassoside (9), centellasaponin A (10), isoasiaticoside (11), scheffoleoside A (12), and centelloside E (13), were separated from the 80% MeOH extract of the whole plant of Centella asiatica, which has been used as a medicinal plant and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…This subtropical tree has very large and relatively thick leaves that contains large amounts of secondary metabolites. Among various phytochemicals, TAs were considered as major products based on the previous research on the chemical composition of S. formosum leaves, and many reports on the biological activities of TAs are available [7,9,15,16]. It is well known that secondary metabolites are affected by environmental factors as well as genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…This subtropical tree has very large and relatively thick leaves that contains large amounts of secondary metabolites. Among various phytochemicals, TAs were considered as major products based on the previous research on the chemical composition of S. formosum leaves, and many reports on the biological activities of TAs are available [7,9,15,16]. It is well known that secondary metabolites are affected by environmental factors as well as genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the compound terminated cell apoptosis, improved the mRNA expression of antioxidant enzymes and facilitated the activation of the phosphatidylinositol 3‐kinase/Akt pathway viz. PDK1, Akt, and GSK‐3β (Wu et al, 2020). Long‐term potentiation (LTP) (6 weeks) using C. asiatica extract (100 mg kg −1 ) before induction of The nucleus basalis of Meynert (NBM) lesion and Alzheimer's showed neuroprotection and enhanced memory in a rat model of Alzheimer's disease (Doulah, Mahmoodi, & Borujeni, 2020).…”
Section: Pharmacologymentioning
confidence: 99%
“… 14–16 Many studies have shown that triterpene saponins such as asiaticoside B, madecassoside and parkioside A can react with free radicals and prevent further development of free radical chain reactions, thus exerting antioxidant effects. 17 , 18 Previous reports described that TSAT exhibited superior DPPH radical scavenging activity to single saponins, as well as good antioxidant capacity against lipid peroxidation in rat liver microsomes, and was shown to have superior antioxidant effects to ginseng, schisandra and other saponins. 14 , 15 In addition, TSAT also attenuated D-gal-induced liver damage in aging rats through its antioxidant effect.…”
Section: Introductionmentioning
confidence: 99%